Cervical Neurinoma Encasing Vertebral Artery - Seddighi, Afsoun; Seddighi, Amir Saied; SadeghAzar, Maryam; Zohreh Vand, Amir Hossein (International Clinical Neuroscience Journal, 2014)
Our case was a 48-year-old man with cervical pain radiatingto the upper limbs. Imaging showed an intradural tumor with extradural component encasing the vertebral artery.Thetumor diagnosed asa neurinomaand had been removed surgically.The post operationmagnetic resonance imagingshowed that the tumor was completely removed andthe vertebral arterywas intact at theentire length.The goal of surgery of neurinoma is a total removal of the tumor,however if the vertebral artery is completely encasing by the tumor, it is advisable to remove the tumor to the level that the vertebral intactness issaved.